TANTANGAN PEMBELAJARAN PAI DI PERGURUAN TINGGI UMUM - SITI NURMELA; UUS RUSWANDI; BAMBANG SAMSUL ARIFIN (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
Various foundations and policies have been seen to support the implementation of Islamic Religious Education, including the implementation of Islamic Religious Education in Public Higher Education. However, in its implementation, Islamic Religious Education (PAI) learning in Public Higher Education faces various complex challenges. This research aims to identify and describe various challenges, especially the challenges of learning Islamic Religious Public Higher Education, as well as approaches and strategies for dealing with them. This type of research is a type of qualitative research with a library study method. The results of this research show that the challenges of PAI learning in Public Higher Education include curriculum challenges, learning implementation challenges, student input challenges, challenges of the impact of globalization, challenges of stigma towards PAI courses, challenges to the position of Islamic education in the National Education System, challenges of the educational environment that provide space for radicalism or liberalism movements, challenges to the competence of PAI lecturers, challenges of learning methods, challenges of Islamic Religious Education orientation, challenges of preparation and selection strategies material PAI, deepening and expanding challenges semantics and genetics are key and basic terms in religious teachings. To face these various challenges, the right approach and strategy are needed.